How the Digital Endorsement Campaign Affects Student’s Attitude towards a Cinema Theater Brand: The Case of #JajanAsyikXXI on Instagram - Wahyuni Pudjiastuti; Qisti Qasthari (Graduate School of Communication Universitas Bakrie, 2024)
The rapid number of social media users and changes in consumer behavior today requires marketers to adapt quickly. The use of celebrity endorser